2014
DOI: 10.1177/1754337114526587
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effects of accelerated weathering and linear drop impact exposures of an American football helmet outer shell material

Abstract: American football helmets are subjected seasonally to a myriad of environmental conditions from expected use and storage and yet are reused without a relational understanding between service life degradation and changes in impact performance. Comprehensive investigations could link rates and degrees of material degradation to scientifically and clinically meaningful changes in helmet performance. Therefore, the purpose of this research was to preliminarily quantify the effects of accelerated weathering on (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
(151 reference statements)
0
1
0
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24][25][26][27] To save financial and temporal costs in the development phase of novel helmet component designs, it is necessary to evaluate the performance of individual components prior to integrating new components into existing helmet systems. Previous research has evaluated the performance of the external helmet shell, 15,[18][19][20]26 the internal padding, 17,[21][22][23]27,28 and the chin strap, 24,25 but the impact performance of a football facemask has received limited research attention. On field impact exposure research has demonstrated that 30%-40% of a season's worth of football head impacts occur to the front quadrant of the helmet system.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27] To save financial and temporal costs in the development phase of novel helmet component designs, it is necessary to evaluate the performance of individual components prior to integrating new components into existing helmet systems. Previous research has evaluated the performance of the external helmet shell, 15,[18][19][20]26 the internal padding, 17,[21][22][23]27,28 and the chin strap, 24,25 but the impact performance of a football facemask has received limited research attention. On field impact exposure research has demonstrated that 30%-40% of a season's worth of football head impacts occur to the front quadrant of the helmet system.…”
Section: Introductionmentioning
confidence: 99%